The Relationship Between Period Poverty Levels and Menstrual Hygiene Management Among Female Students of the Faculty of Economics and Business, Gorontalo State University - Deivi Margrit Shufairoh M. Kau; Ika Wulansari; Nur Fitriah Jumatrin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyse the relationship between the level of period poverty and menstrual hygiene management among female students at the Faculty of Economics and Business, Universitas Negeri Gorontalo. The method used was a quantitative study with a cross-sectional design. The sample consisted of 320 female students selected using proportional random sampling. Data were collected using structured questionnaires measuring the level of period poverty and menstrual hygiene management practices. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test at a significance level of 5%. The results showed that most respondents experienced a moderate level of period poverty and the majority demonstrated good menstrual hygiene management practices. Bivariate analysis indicated a significant relationship between the level of period poverty are associated with poorer menstrual hygiene management practice among female university students. Therefore, support from educational institutions and healthcare professionals is needed to improve access to sanitation facilities and menstrual health education.